1992
DOI: 10.1007/bf00300940
|View full text |Cite
|
Sign up to set email alerts
|

Spinal stabilization for patients with metastatic lesions of the spine using a titanium spacer

Abstract: Stabilisation rachidicnnc utilisant un " spacer" eil titane chc7. les palients porteurs de lesions mClastatiqucs dc la eolOllllC vertebrale ResumC. La decompressio n anterieure a ete realiscc chez 41 patienls porteurs de metastases du corps vertebral. Les complications neurologiqucs Claient patentes chez 36 patients el latentes chez 5 d'entre eux. On a urilisc poUT la reconstruction un cylindrc dc litane, mis eil place aprcs la corporectomie cl rCllfo rce par une pl aque anlerieure. L'implant cn tilane peul ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 28 publications
0
6
0
1
Order By: Relevance
“…Bridwell et al [2] observed local recurrence in 6 out of 19 cases of spinal metastasis (31.6%) treated by posterior decompression. According to Hertlein et al [5], no local recurrence was observed when surgery was performed according to the metastatic localization. Local recurrence occurred in 8.4% in our study after an appropriate approach, and was identical for anterior and posterior approaches.…”
Section: Discussionmentioning
confidence: 97%
“…Bridwell et al [2] observed local recurrence in 6 out of 19 cases of spinal metastasis (31.6%) treated by posterior decompression. According to Hertlein et al [5], no local recurrence was observed when surgery was performed according to the metastatic localization. Local recurrence occurred in 8.4% in our study after an appropriate approach, and was identical for anterior and posterior approaches.…”
Section: Discussionmentioning
confidence: 97%
“…However, the designes of such implants still require nowadays extensive surgeries (24,35,36,37,38). Furthermore, these constructions have to be completed by an additional stabilizing implant except the prosthesis discussed by MACMILAN et al (35).…”
Section: Discussionmentioning
confidence: 98%
“…Alternative techniques have been described by: SALZER et a!. (1988), TuRNER et al (1988),MANABE et al (1989, MOORE and UTTLEY (1989), CYBULSKI (1989), GALASKO (1991), KANEDA (1991) Fidler et al (1991), HARMS (1992), HERTLEIN et al (1992), COOPER eta!' (1985), SIEGAL (1985, 1990), HARRINGTON (1986), ONIMUS et al (1986) , STEFFEE et al (1986) MA et al (1987, KOSTUIK et al (1988), MAGERL and COSCIA (1988), ONO et a!.…”
Section: Surgical Techniques For Metastases At Various Spinal Levelsmentioning
confidence: 99%